2016
DOI: 10.1007/s00284-016-1075-z
|View full text |Cite
|
Sign up to set email alerts
|

Photo Inactivation of Streptococcus mutans Biofilm by Violet-Blue light

Abstract: Among various preventive approaches, non-invasive phototherapy/photodynamic therapy is one method used to control oral biofilm. Studies indicate that light at specific wavelengths has a potent antibacterial effect. The objective of this study was to determine the effectiveness of violet-blue light at 380-440 nm to inhibit biofilm formation of Streptococcus mutans or kill S. mutans. S. mutans UA159 biofilm cells were grown for 12-16 h in 96-well flat-bottom microtiter plates using Tryptic Soy broth (TSB) or TSB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Another study of aBL inactivation of S. mutans biofilm was carried out by Gomez et al (Gomez et al, 2016). In the study, biofilms cultured in 96-well microtiter plates were exposed to aBL (380–440 nm, peak emission 405 nm) at an exposure of 9.26 J/cm 2 .…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…Another study of aBL inactivation of S. mutans biofilm was carried out by Gomez et al (Gomez et al, 2016). In the study, biofilms cultured in 96-well microtiter plates were exposed to aBL (380–440 nm, peak emission 405 nm) at an exposure of 9.26 J/cm 2 .…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…In another study, Gomez et al irradiated initial biofilms (λ = 380-440 nm with 405-nm peak) formed by strains of S. mutans grown for 12-16 h [35]. Intensity on surface was 13 mW/cm 2 and irradiation was done for 5 min, resulting in a fluence of 9.26 J/cm 2 .…”
Section: Streptococcus Sppmentioning
confidence: 99%
“…In our previous study, we demonstrated photoinactivation of S. mutans with 5 min of violet-blue light treatment by quantitatively determining the viability (colony-forming units) of biofilm cells (15). In this study, we found decreased metabolic activity of violet-blue light-treated S. mutans at 0-h and 2-h recovery periods, providing an indirect estimation of cell viability.…”
Section: Discussionmentioning
confidence: 53%
“…The metabolic activity of TSBS S. mutans remained unaffected after 6-h recovery period and was increased compared with 0-h recovery period. We previously reported that there was no difference in biofilm formation with respect to light treatment after the 6-h reincubation period in the TSBS group, which suggests that the bacterial cells are viable (15). Bacterial cells, however, which are encompassed within extracellular glucans, may be improperly reduced by tetrazolium salts (19) in the assay used in this study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation